(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The goal - the present article is the collection, compilation and evaluation of the main methods of treatment of patients with cholelithiasis complicated by choledocholithiasis . Analysis of such information will make it possible to improve previously developed devices, as well as to create techniques and devices, the main advantage of which will be a decrease in injuries during surgical treatment options and a decrease in the number of complications.